Arbuscular Mycorrhizal Association for Growth and Nutrients Assimilation of Pharagmites japonica and Polygonum cuspidatum Plants Growing on River Bank Soil. Issue 1 (2nd January 2016) - Sarkar, Animesh; Asaeda, Takashi; Wang, Qingyue; Rashid, Md. H.
ABSTRACT: Effects of arbuscular mycorrhizal fungi (AMF) on the growth, nutrient absorption, and inoculation effectiveness of AMF on pioneer plants Pharagmites japonica (C4) and Polygonum cuspidatum (C3) were evaluated by performing a pot experiment in a greenhouse at Saitama University, Japan. AMF spores were collected from the commercial product, Serakinkon. The average colonization levels of P. japonica and P. cuspidatum were 24–33% and 0.2–0.5% respectively and no colonization was found in sterilized soil treatment. AMF colonization increased the plant dry mass, phosphorus (P), and nitrogen (N) concentrations of P. japonica 's roots, stems, and leaves when AMF applied with natural and sterilized soil compared with only sterilized and natural soil. This was a significant effect for N-loss minimization from soil. Maximum value showed when P. japonica was grown with natural soil in combination with AMF whereas P. cuspidatum showed very less or a negative response to AMF colonization in all cases.